2015
DOI: 10.1093/annonc/mdu552
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from second-line therapy in long-term responders to first-line tyrosine kinase inhibitor in clear-cell metastatic renal cell carcinoma

Abstract: m-ccRCC patients who remained on first-line TKI between 11 and 22 months benefited from a TKI rechallenge rather than from second-line mTORi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…mOS was not reached for ORR (RC+RP), the mean OS according to DCR and ORR was 14.95 and 15.66 vs. 7.4 and 7.42 months, respectively. Our results are consistent with those of Elaidi et al who conducted a retrospective analysis of 241 m-ccRCC patients who received a first-line TKI for ≥6 months followed by a second-line TKI or mTORi, showing that patients who remained on first-line TKI between 11 and 22 months benefited from a TKI rechallenge rather than from second-line mTORi (PFS [HR≈0.5; median PFS (months): 9.4 (5.9–12.2) vs. 3.9 (3.0–5.5), p = 0.003; TTF(months): 8.0 (5.5–11.0) vs. 3.6 (3.0–4.6), p = 0.009]; Elaidi et al, 2015 ). Historically, VEGF-targeted therapy was reported to achieve higher ORR (20–30%) compared to mTOR-targeted therapy (≤ 10%), which is supported by our analysis (Grünwald et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…mOS was not reached for ORR (RC+RP), the mean OS according to DCR and ORR was 14.95 and 15.66 vs. 7.4 and 7.42 months, respectively. Our results are consistent with those of Elaidi et al who conducted a retrospective analysis of 241 m-ccRCC patients who received a first-line TKI for ≥6 months followed by a second-line TKI or mTORi, showing that patients who remained on first-line TKI between 11 and 22 months benefited from a TKI rechallenge rather than from second-line mTORi (PFS [HR≈0.5; median PFS (months): 9.4 (5.9–12.2) vs. 3.9 (3.0–5.5), p = 0.003; TTF(months): 8.0 (5.5–11.0) vs. 3.6 (3.0–4.6), p = 0.009]; Elaidi et al, 2015 ). Historically, VEGF-targeted therapy was reported to achieve higher ORR (20–30%) compared to mTOR-targeted therapy (≤ 10%), which is supported by our analysis (Grünwald et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, results of a subanalysis of the AXIS trial and a retrospective analysis have suggested that response to first-line VEGF-targeted therapy is not associated with response to second-line VEGF-targeted therapy [16,17]. A retrospective study of patients with mRCC who received a first-line VEGFR-TKI for P6 months followed by either a second VEGFR-TKI or an mTOR inhibitor reported in favour of sequential VEGFRTKIs, but the benefit was largely attributed to patients who received the first agent for 11-22 months [18]. At this time, the correlation between response to a first-line VEGF-targeted agent and second-line VEGF-targeted agent or mTOR inhibitor remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the m-TKI cabozantinib, which inhibits c-MET, RET, and VEGFR, showed efficacy in patients with RR-DTC refractory to at least one prior VEGFR-targeted therapy [13]. Sequential treatment with m-TKIs has also shown efficacy in patients with metastatic renal cell cancer [14,15]. Also in our present patient, sorafenib showed efficacy after she had received lenvatinib for about 3 years and she was unable to tolerate lenvatinib.…”
Section: Discussionmentioning
confidence: 66%